REFRAMING THE ORGANIZATION: WHY IMPLEMENTING TOTAL QUALITY IS EASIER SAID THAN DONE - Reger, Rhonda K.; Gustafson, Loren T.; Demarie, Samuel M.; Mullane, John V. (Academy of Management Review, 1994)
Rhonda K. Reger, Loren T. Gustafson, Samuel M. Demarie, John V. Mullane, Reframing the Organization: Why Implementing Total Quality is Easier Said Than Done, The Academy of Management Review, Vol. 19, No. 3, Special Issue: "Total Quality" (Jul., 1994), pp. 565-584